Condition-Based Monitoring of Kiln Induced Draft Fan in A Dry Process Cement Plant for Efficient Utilization - Adetunji, Olayide R.; Sokunbi, Idowu O.; Kuye, Sidikat I.; Adesusi, Olanrewaju M.; Okediran, Iliyas K. (Journal of Advanced Industrial Technology and Application, 2023)
Associated downtime and economic loss caused by replacement/maintenance of equipment necessitated pro-active technique known as Condition-Based Monitoring to prevent/reduce failures. This study evaluated the vibration of Kiln Induced Draft (KID) of cement plant before and after failure. Vibration data was acquired using accelerometer probe and data obtained were analyzed statistically by employing t-Test at 95% confidence. Results showed that vibration signals measured in mm/s for KID motor and fan bearings (non-drive and drive ends) in the horizontal plane recorded higher values than vertical and axial planes when measured before failure occurrences. After failures, horizontal plane values increased by more than 120% while those measured in the vertical and axial planes increased by less than 100%, making horizontal plane vibration measurement a more suitable parameter for predicting the machinery health condition. The t-Test conducted showed that mean differences in values of vibration signal data before and after failure are not zero but negatives (signal before failure < signal after failure). Outputs from tests of significance using two-tailed t-Test indicated that the differences in values of vibration data signals are not significant at (p? 0.05) when considering “equal variance not assumed”. The non-significance of these mean differences may indicate that the present operational vibration signal level should be maintained at values in order that significant difference may be observed between periods before failure and after failure for efficient prediction of failure, as the present 1.5-3.5 mm/s range is likely not a good range for efficient failure prediction.